Pregnant Women's Knowledge About Early Detection of Preeclampsia at The Akbar Medica Clinic Mojokerto Regency - Nurhayati, Nunuk (Journal of Scientific Research, Education, and Technology (JSRET), 2025)
Preeclampsia and eclampsia rank second in the world as a contributor to maternal mortality and morbidity. Preeclampsia is a serious health problem and has a high level of complexity because its impact is not only on the mother during pregnancy and childbirth, but also on the baby. Every pregnancy has a risk of complications, so identifying risk factors for preeclampsia is an important priority. The type of research used is descriptive research. The sample used was 30 pregnant women in the first and second trimesters in the Akbar Medika Clinic working area from January to September 2025. The results showed that of the 30 pregnant women, most of them had insufficient knowledge about early detection of preeclampsia, as many as 50% (15 mothers). This was influenced by the age of mothers aged <20 years as many as (5 mothers) 100%, from those with basic education had insufficient knowledge as many as (7 mothers) 77.8%. Of the 22 mothers, 73.3% were unemployed. Lack of knowledge about preeclampsia among pregnant women can lead to their inability to recognize the early signs and symptoms of this condition. As a result, when they experience symptoms such as swelling, hypertension, or visual disturbances, they may dismiss them as not serious or as normal. This risks delaying treatment and increasing the risk of complications for both mother and fetus..